Tantangan dalam implementasi social entrepreneurship pariwisata di Pulau Madura - Dian Yulie Reindrawati (Masyarakat, Kebudayaan dan Politik, 2017)
Social entrepreneurship in Indonesia faced the trend of opportunity negligence for local people to participate in tourism development in their area. The positive economic impact of tourism often enjoys by outsiders. This paper examines the challenges in the implementation of social entrepreneurship in Madura, includes challenges faced by the Madurese community in developing their social entrepreneur spirit and business. This study draws on in-depth interviews held with 31 residents. It was found that social entrepreneurship is mostly initiated by the local people. Lack of support from the government in developing social entrepreneurship is reported by the participants as one challenge they face in developing social entrepreneurship. Findings of this study are inconsistent with the assumption that local community participation in tourism is paramount in tourism development. These findings will serve a ‘wake-up call’ for the Indonesian government to pay more attention to incorporate the local community in tourism development process, particularly in giving the locals a room to develop their social entrepreneur spirits as well as providing adequate support for their social entrepreneurship business to grow.